E-CRM as a catalyst for brand awareness and engagement: A strategic imperative for private institutes of higher learning in Malaysia - Abdullah, Siti Salmiah; Abdul Wahid, Nur Kamariah (International Journal of Accounting, Finance and Business, 2025)
The emergence of E-commerce has ushered in a multitude of advantages, especially in terms of economic development. Even before the COVID-19 pandemic, Private Institutes of Higher Learning (IHLs) have faced significant challenges and intense competition including Malaysian Private IHLs. In response, these institutions have implemented various strategies to sustain their competitiveness in the education sector. Among these strategies, marketing management has emerged as a crucial approach, providing a comprehensible platform for cultivating market relations within the academic domain. This paper delves into the realm of electronic customer relationship management (e-CRM) in the private higher education sector, focusing on the impact of digital transformation on brand image. With the advent of e-commerce and the evolving expectations of tech-savvy students, establishing and maintaining a strong brand image has become crucial for private IHLs. This article explores the pivotal role of e-CRM to Malaysian Private IHLs in enhancing brand awareness and engagement as well as presents it as a strategic imperative for businesses. Drawing on theoretical frameworks and empirical evidence, this research article provides insights into how businesses can leverage e-CRM to elevate their brand image, build customer trust, and foster long-term relationships. By understanding the significance of e-CRM as a catalyst for brand awareness and engagement, IHLs can develop effective strategies to thrive in today's dynamic marketplace.